1999
DOI: 10.1029/1999gl900335
|View full text |Cite
|
Sign up to set email alerts
|

On the photochemical production of new particles in the coastal boundary layer

Abstract: Abstract.Concurrent measurements of ultra-fine (r<5 nm)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
178
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(190 citation statements)
references
References 11 publications
12
178
0
Order By: Relevance
“…Our current understanding of atmospheric nanoparticle processes suggests that growth of these particles to larger sizes within the ultrafine PM mode occurs by condensation of low volatility organic species. These species are products of photochemical oxidation of volatile organic precursors on these pre-existing nuclei (O'Dowd et al, 1999;Kulmala et al, 2004). In fact, recent studies by Zhang et al (2004) showed that nucleation rates of sulfuric acid are greatly increased in the presence of organic acids (including products of atmospheric photochemical reactions), by forming unusually stable organic-sulfuric acid complexes, thereby reducing the nucleation barrier of sulfuric acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our current understanding of atmospheric nanoparticle processes suggests that growth of these particles to larger sizes within the ultrafine PM mode occurs by condensation of low volatility organic species. These species are products of photochemical oxidation of volatile organic precursors on these pre-existing nuclei (O'Dowd et al, 1999;Kulmala et al, 2004). In fact, recent studies by Zhang et al (2004) showed that nucleation rates of sulfuric acid are greatly increased in the presence of organic acids (including products of atmospheric photochemical reactions), by forming unusually stable organic-sulfuric acid complexes, thereby reducing the nucleation barrier of sulfuric acid.…”
Section: Discussionmentioning
confidence: 99%
“…During summer months, secondary aerosol formation is favored and new ultrafine particles may form as a result of the condensation of low-volatility products of photochemical reactions (largely organic compounds) onto stable, nanometer-size particles (O'Dowd et al, 1999;Kim et al, 2002;Sardar et al, 2004). Secondary aerosol formation is the most likely explanation for the diurnal trends in PN during the summer period at USC and Long Beach (Figures 4b and 5b, respectively) in which the peak particle concentrations during the afternoon period either coincide or slightly lag behind the peak in O 3 concentrations.…”
Section: Diurnal Trendsmentioning
confidence: 99%
“…[13] Newly formed particles by homogeneous nucleation of water and sulfuric acid, in presence of ammonia and other organic species, tend to have very small sizes (d p $ 2 nm) [Covert et al, 1992;Mäkelä et al, 1997;Marti et al, 1997;Weber et al, 1997Weber et al, , 1998Kulmala et al, 1998;O'Dowd et al, 1999;Clarke et al, 1998]. It has been shown that the nucleation rate can be enhanced by the presence of organics and ions [Yu et al, 1999;Yu and Turco, 2000].…”
Section: Growth Rate Of Ufpmentioning
confidence: 99%
“…[7] Two types of nucleation events have been observed in which the main condensing species are not sulfuric acid and ammonia: in Finnish forests [Mäkelä et al, 1997] and off the Irish coast [O'Dowd et al, 1999]. Their characteristics, covering many events, have been explored in large cooperative European campaigns, Biogenic Aerosol Formation in the Boreal Forest (BIOFOR) and New Particle Formation and Fate in the Coastal Environment (PARFORCE), whose results have recently been reported [Kulmala and Hämeri, 2000;O'Dowd and Hämeri, 2000].…”
Section: Previous Workmentioning
confidence: 99%